Product Placement Effectiveness in a Bollywood Movie with Debutant Actors: A Case Study - Sharma, Sneha; Chadha, Suresh K.; Goyal, B. B. (Indian Journal of Marketing, 2014)
India has one of the world’s biggest movie industries in terms of the number of movies produced every year. Product placement has always been an interesting topic of discussion with reference to the movies as well as TV serials/commercials. The dual purpose of this study was to ascertain the perception of the respondents towards debutant actors and to examine the relationship between product placement effectiveness and debutant actors. Experimental design was used for conducting the research. A sample of 52 students was shown a movie clip of the movie Student of the Year as it had three debutant actors and was well received by the student community. The results revealed that the actors were basically judged on two major criteria - Charisma and Credibility. The effectiveness of different forms of product placement, that is, implicit product placement, integrated explicit product placement, and non integrated explicit product placement were analyzed. The results showed a difference in the recall rates of the three types of product placements. For all the three types of placement, the viewers recall, that is, implicit memory measurement and explicit memory measurement received no impact from the feelings of the respondents towards the debutant actors. The results from the current study also put forward that the debutant actors had no significant effect on product placement. Thus, the major objective of the study, that is, finding out the impact of debutant actors on product placement effectiveness gave interesting results, where star presence was found to have no effect on product placement.